Modelling remedies to waqf liquidity constraints: The case of waqf unit trust model (WUTM) - Ahmad Khaliq; Mohamed Asmy Mohd Thas Thaker; Hassanuddin Mohd Thas Thaker; Anwar Allah Pitchay; Mohamad Isa Abd Jalil (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2025)
The history of the waqf institution is rich with impressive achievements that cover each phase of socio-economic life and human development. However, recent initiatives among local waqf institutions indicate that the liquidity limitation contributes as the core concern to cultivating further development undertakings. This research aims to offer a sustainable source of financing through the application of the waqf unit trust model (WUTM) for local waqf institutions in mitigating their liquidity constraint to cultivate waqf undertakings such as land rejuvenation, health sector improvement, educational sector enhancement and other critical necessities. Specifically, this study aims to discover the liquidity constraints needed in waqf institutions in Malaysia, to propose an alternate WUTMin fostering liquidity of waqf assets, and to explore the pertinent stakeholders’ stance on the feasibility of the model proposed. This research employs in-depth interview methods for data collection with the waqf practitioners such as authorities from the State Islamic Religious Council (SIRC), financial consultants linked to capital market development, academicians engaged with waqf-related projects, and regulators of Islamic capital market stationed in Klang Valley (the State of Selangor and Federal Territory of Kuala Lumpur), Penang and Johor state of Malaysia. Findings propose the craft of the WUTM framework could potentially assist in liquidity pooling, cash flow solutions and generate continuous income and wealth. This study contributes to the body of knowledge by offering a potential remedy for the liquidity constraint faced by waqf institutions.